2020
DOI: 10.1186/s12882-020-01930-6
|View full text |Cite
|
Sign up to set email alerts
|

Severe euglycemic diabetic ketoacidosis of multifactorial etiology in a type 2 diabetic patient treated with empagliflozin: case report and literature review

Abstract: Background Sodium-glucose co-transporter-2 (SGLT-2) inhibitors are a relatively novel class of oral medications for the treatment of Type 2 DM with a generally acceptable safety profile. However, these agents have been associated with rare events of a serious and potentially life-threatening complication named euglycemic diabetic ketoacidosis (euDKA). euDKA is not identical with the typical diabetic ketoacidosis, as it often presents with serious metabolic acidosis but only mild to moderate glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The majority of the authors reported EDKA in middle-aged women with long-standing T2DM, body mass index between 35 and 40 kg/m 2 , and who had been on multiple doses of SGLT2i for at least more than three months [34][35][36]. The common presenting complaints were fatigue, abdominal pain, shortness of breath, reduced food intake, nausea, and vomiting.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the authors reported EDKA in middle-aged women with long-standing T2DM, body mass index between 35 and 40 kg/m 2 , and who had been on multiple doses of SGLT2i for at least more than three months [34][35][36]. The common presenting complaints were fatigue, abdominal pain, shortness of breath, reduced food intake, nausea, and vomiting.…”
Section: Pathophysiologymentioning
confidence: 99%
“…On examination, they were tachypneic, with tachycardia, blood glucose less than 200 mg/dL, blood pH <7.3 (7.08-7.2), increased anion gap, and increased blood ketones, such as beta-hydroxybutyrate and serum acetone. Sampani et al reported increased ketones in the urine as well [ 34 ]. The precipitating factors, signs and symptoms, and diagnostic criteria are depicted in Figure 3 [ 2 , 7 - 10 , 20 - 32 , 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…DKA is a serious complication of diabetes that is commonly observed in both T1DM and T2DM patients, especially under extreme physical stress such as trauma, surgery, or infection [ 2 , 8 , 9 ]. Persistent acidosis may be commonly seen after resolution of DKA due to hyperchloremic acidosis from resuscitation with fluids containing zero strong ion difference.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting beta hydroxybutyrate (β-HB) levels are doubled after empagliflozin administration, as reported by Ferranini et al . [ 2 , 10 ], as there is a rise of β-HB due to overproduction and, hence, both clearance rate and fractional excretion of β-HB are increased [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation